A avaliação de desempenho por competência da Universidade Federal da Paraíba, como intrumento de gestão – uma análise sob a ótica de seus atores - Carvalho, James Madison Cavalcanti de (2021)
The performance evaluation has become a commonplace fact in our lives and in organizations as well. People are, all the time, evaluating each other and the things around them. One of the biggest challenges in people management in the public service is precisely to define the most appropriate form of performance and productivity assessment to be used in each institution to which the civil servants are linked. This research aims to perceive subsidies that can contribute to the definition of a method and more effective ways of measuring performance by competence at the Federal University of Paraiba – UFPB, analyzing the process from the perspective of the main actors involved. The understanding and involvement of these participants are essential factors for carrying out tasks with quality, competence and excellence. We will start from basic questions, supported by theories and that are linked to the research and we will analyze the knowledge, satisfaction, involvement, among other aspects, of employees, about the performance evaluation process and agreement with the evaluation policies in force, as well as the compliance with the performance evaluation process with the proposed purposes, its effectiveness and effectiveness in improving the provision of services, both to the internal and external public, in line with the institution's objectives, in addition to its importance in balancing the training plan used in the UFPB.